2021
DOI: 10.4293/jsls.2020.00091
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Hysterectomy for Benign Indications: What Have We Learned from a Decade?

Abstract: Background and Objectives: Robotic surgery data need a setback on many years of practice with high-volume surgeons to evaluate its real value. Our main objective was to study the impact of a decade of robotic surgery on minimally-invasive hysterectomies for benign indications. Our secondary objectives were to evaluate our results for high-volume surgeons and complex cases. Methods: In this retrospective cohort study, we reviewed medical records at Foch Hospital, from 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…In the period 2005-2013, abdominal hysterectomy declined from 59% to 22% according to premier perspective database [9] and by 2012 the hysterectomies performed by minimally invasive surgery rose to 75% [10]. This was associated with parallel increase in RH which increased from 26% to 61% and the same study and showed that high-volume surgeons were more efficient and showed a decrease in OR time after 75 cases despite an increase in uterine weight [11].…”
Section: Discussionmentioning
confidence: 83%
“…In the period 2005-2013, abdominal hysterectomy declined from 59% to 22% according to premier perspective database [9] and by 2012 the hysterectomies performed by minimally invasive surgery rose to 75% [10]. This was associated with parallel increase in RH which increased from 26% to 61% and the same study and showed that high-volume surgeons were more efficient and showed a decrease in OR time after 75 cases despite an increase in uterine weight [11].…”
Section: Discussionmentioning
confidence: 83%
“…The previous increase in the number of publications found in our study is in line with the ongoing increased rate of robotic surgery in gynecology. The rate of hysterectomies performed robotically has increased parallel to a decrease in abdominal hysterectomies, as well as conventional laparoscopic and vaginal hysterectomies, during the last two decades [ 34 36 ]. The rate of myomectomies performed robotically has also increased since 2012 [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the study lacked power, with no preliminary effective calculation and non-comparable groups, the subgroups analysis showed that there was a greater improvement in quality of life, slightly greater in RL compared to the CL group. Most studies show no difference between the two courses of surgery except for operative length, which tends to be longer for robotic laparoscopy, and a tendency of decreased bleeding with robotic surgery [ 21 ]. The cost of robotic surgery also needs to be balanced with the surgeon’s comfort [ 22 ].…”
Section: Discussionmentioning
confidence: 99%